2018
DOI: 10.1155/2018/8637498
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Practice in Sleep Management: A Review of Conceptual Models and Research Evidence

Abstract: The effectiveness of sleep intervention developed by occupational therapists was reviewed, and a conceptual framework for organizing the developing practice of sleep management in occupational therapy was proposed in this paper. Evidence-based articles on sleep management practice in occupational therapy from 2007 to 2017 were retrieved. Four types of effective sleep management intervention were identified from the literature, including the use of assistive devices/equipment, activities, cognitive behavioral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 29 publications
(94 reference statements)
0
24
0
1
Order By: Relevance
“…In this study, the restructuring of daytime activity despite physical limitation and engagement in all aspects of occupation may result in a reduction of stress and a sense of better health. 32 Therefore, the intervention can be considered to be effective from an OT perspective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the restructuring of daytime activity despite physical limitation and engagement in all aspects of occupation may result in a reduction of stress and a sense of better health. 32 Therefore, the intervention can be considered to be effective from an OT perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention programs in each group were as follows: Patients receive care-as-usual plus intervention (CAU + Intervention): Since, currently, no evidence exists to support an occupational therapy-based intervention for sleep problems in patients with MS, this intervention was designed according to a review of the literature, with careful consideration given to the scoping review by Leland et al 23 (2014) and Ho et al 32 (2018) on the role of occupational therapists in the treatment of sleep problems. The intervention used in the current study was compromised of a combination of common interventions used for patients with sleep problems, including patients with MS and those receiving occupational therapy interventions.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep quality is defined by the amount of sleep time, sleep efficiency, total sleep duration and percentage of deep sleep [19] and the lack of quality sleep is often associated with work, family and leisure-related demands [22][23][24]. Other factors that may also affect sleep quality negatively include stress, dissatisfaction with work, high blood pressure and pain syndromes resulting from musculoskeletal problems or neurological diseases [25,26]. People who sleep poorly often more frequently take sick leave and have an inferior physical and mental health status compared to people who sleep well [27].…”
Section: Sleepmentioning
confidence: 99%
“…Studies have shown that strategies such as focussing on the bedroom environment, i.e. providing adaptive equipment to modifying the environment may improve sleep, for example, a quiet and dark sleep environment [26].…”
Section: Practical Implication and Further Studiesmentioning
confidence: 99%